Severe Sequelae to Mold-Related Illness as Demonstrated in Two Finnish Cohorts - Tuuminen, Tamara; Rinne, Kyösti Sakari (Frontiers in Immunology, 2017)
The presence of toxic indoor molds with accompanying bacterial growth is clearly detrimental to 16 human health. The pathophysiological and toxicological effects of toxins and structural 17 components of molds and bacteria have been clarified in experiments conducted in tissue culture 18 and animals and there is convincing epidemiologic evidence; nonetheless their implications for 19 human health are either ignored or denied, at least in Finland. In this communication, we 20 describe two cohorts suffering severe sequelae to mold-related illness. One cohort is a 9-member 21 family with pets that moved into a new house which soon proved to be infested with pathogenic 22 molds. The other cohort consists of 30 teachers and 50 students from a mold-infested school 23 building. The first cohort experienced a plethora of mucosal irritation, neurological, skin, allergic 24 and other symptoms, with all family members ultimately developing a multiple chemical 25 syndrome. In the second cohort, we detected a greatly elevated prevalence of autoimmune 26 conditions and malignancies. We claim that mold-related illness exists in multiple facets; it not 27 simply a transient mucosal irritation or even an increased risk of asthma onset or its 28 exacerbation. We propose a scheme to explain the natural course of the mold-related illness. We 29 recommend that future studies should combine data from e.g. cancer, autoimmune, endocrine 30 disorder registers, with mold-exposed individuals being monitored for prolonged follow-up 31 times.